Knowledge spillovers in the mutual fund industry through labor mobility - Gjergji Cici; Alexander Kempf; Claudia Peitzmeier (University of Cologne, Centre for Financial Research (CFR), 2019)
Firms' competitive advantages are unsustainable when competitors poach their employees away to study and recreate those advantages. We document inter-firm knowledge spillovers through labor mobility in the mutual fund industry. About one quarter of the competitive advantage of the originating fund family spills over to the recipient family. These knowledge spillovers intensify when switching managers had better access to the organization processes of the originating family and frictions hampering knowledge absorption are weaker. Ease of knowledge integration, greater organizational similarity, and lower information barriers at the recipient family—acting as mitigants for the aforementioned frictions—also magnify these knowledge spillovers.
Keywords: D86; G23; K12; K31; M5; 330; organization capital; knowledge spillovers; mutual funds; learning-by-hiring